Research on a Curvature-Enhanced and Synergistic Attention-Based Multi-Task Perception Method for Transparent Objects - Han, Jiajin; Deng, Sanpeng; Qi, Yuming; Shi, Xiumin (International Journal of Computer Science and Information Technology, 2026)
Transparent objects challenge monocular perception due to refraction, reflection, and weak textures, which hinder accurate depth estimation and segmentation. To overcome these issues, we propose CESINet, a curvature-enhanced synergistic attention network for transparent object perception. CESINet explicitly incorporates surface curvature as a high-order geometric prior to strengthen spatial representation and introduces a curvature-guided synergistic attention module to enable effective cross-task feature interaction between depth and segmentation branches. A curvature consistency loss further enforces geometric coherence across predictions. Experiments on the ClearPose dataset show that CESINet achieves 94.33% mIoU and 98.27% mAP for segmentation, improving over the multi-task baseline ISGNet by 1.49% and 0.44%, respectively. For depth estimation, CESINet attains an RMSE of 0.112 and REL of 0.060, reducing errors by 8.9% and 11.8% compared with the baseline. Ablation results demonstrate that removing curvature priors or attention modules leads to performance drops of up to 3.5% in segmentation and 12% in depth accuracy, confirming the complementary benefits of explicit geometry and synergistic learning. Overall, CESINet enhances geometric consistency and boundary sharpness while maintaining computational efficiency, providing a unified and scalable framework for multi-task transparent object understanding.